PERAN EMOSI POSITIF PADA SISWA MENGGUNAKAN TEKNIK POSITIVE REINFORCEMENT PERSPEKTIF NEUROSAINS - Jannah, Widya Faridhatul; Suyadi, Suyadi; Hadiyanto, Anniza Wiwied Rahayu; Suyoto, Suyoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study reviewed the role of positive emotions in elementary school students that can be used to optimize the use of positive reinforcement techniques in learning. The research method used is the study of libraries using a qualitative approach. Methods of data collection related to theoretical surveys and references related to cultures, values, and norms relevant to the situation being studied. Data collection method using electronic books, scientific journals, and other scientific literature. In the context of neuroscience, positive emotions of students can affect the activity and balance of the limbic system, including parts of the brain that are associated with emotions, motivation, and learning. Positive emotions have a beneficial effect on the nerve pathways involved in mood regulation, motivation and cognitive function. A good mood such as being happy, confident, proud, building a positive learning environment can be formed from a variety of positive reinforcement techniques that teachers give to students. The use of this positive reinforcement technique is able to highlight the motivation, and student learning achievement because this technique can cultivate positive emotions of students.